2016
DOI: 10.1016/j.atherosclerosis.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein subclass measurements improve mortality risk prediction, discrimination and reclassification in a cardiac catheterization cohort

Abstract: Background and Aims Recent failures of HDL cholesterol (HDL-C)-raising therapies to prevent cardiovascular disease (CVD) events have tempered the interest in the role of HDL-C in clinical risk assessment. Emerging data suggest that the atheroprotective properties of HDL depend on specific HDL particle characteristics not reflected by HDL-C. The purpose of this study was to determine the association of HDL particle concentration (HDL-P) and HDL subclasses with mortality in a high-risk cardiovascular population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 42 publications
7
54
1
2
Order By: Relevance
“…In our cohort, HDL particle size is associated with mortality risk—larger HDL size confers a higher risk of mortality and a sum of small- and medium-size HDL particles (MS-HDL-P) confers a lower risk (7). In studies from other groups the antiinflammatory properties of HDL become proinflammatory during the acute-phase response (22); this suggests a potential interaction between HDL and inflammation that could influence mortality risk.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In our cohort, HDL particle size is associated with mortality risk—larger HDL size confers a higher risk of mortality and a sum of small- and medium-size HDL particles (MS-HDL-P) confers a lower risk (7). In studies from other groups the antiinflammatory properties of HDL become proinflammatory during the acute-phase response (22); this suggests a potential interaction between HDL and inflammation that could influence mortality risk.…”
Section: Resultsmentioning
confidence: 91%
“…Lipoprotein subclass particle concentrations and size are also measurable by NMR spectroscopy and are independent markers of CVD (6, 7). Emerging preclinical and clinical data suggest a biological interaction between inflammation and HDL.…”
mentioning
confidence: 99%
“…These findings confirm that total HDL-C level does not necessarily reflect the athero-protective properties of HDL. Interestingly, one study published this year concluded that smaller, denser HDL3-C levels are primarily responsible for the inverse association between HDL-C and incident CHD (23) and the other concluded that the small and medium size HDL particle measurements improve mortality risk prediction (24). These studies lend further support to the concept that the smaller, denser HDL subpopulation is superior to total HDL in risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pharmacological interventions aimed at raising HDL-cholesterol levels failed to reduce cardiovascular events [3,4]. Determination of HDL particle concentrations and HDL subclasses as well as determination of HDL functionality have proved more appropriate to test and quantify the beneficial atheroprotective properties of HDL [5,6]. HDL-mediated atheroprotection has been ascribed to the attenuation of endothelial adhesion molecule expression, protection of low-density lipoprotein (LDL) from oxidation, inhibiton of inflammatory response in macrophages, stimulation of endothelial nitric oxide production and promotion of vasodilatation [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%